2019
DOI: 10.1111/jmwh.13007
|View full text |Cite
|
Sign up to set email alerts
|

The Scope of Midwifery Practice Regulations and the Availability of the Certified Nurse‐Midwifery and Certified Midwifery Workforce, 2012‐2016

Abstract: Introduction: Studies have linked midwifery practice laws to the availability of midwives but have generally not related workforce data to potential demand for reproductive health services. We examined state regulatory structure for midwives and its relationship to midwifery distribution and vital statistics data at the state and county level. Methods: Midwifery distribution data came from the Area Health Resources Files, distribution of women of reproductive age came from the US Census, and birth statistics c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 23 publications
6
52
0
1
Order By: Relevance
“…For CNMs specifically, Ranchoff and Declercq (2020) found that restrictive practice environments for CNMs are related to women's access to maternity and reproductive health services from these providers. They further suggest that expanding midwifery practice in states with restrictive environments may significantly improve access to maternity care services.…”
Section: Chaptermentioning
confidence: 99%
See 1 more Smart Citation
“…For CNMs specifically, Ranchoff and Declercq (2020) found that restrictive practice environments for CNMs are related to women's access to maternity and reproductive health services from these providers. They further suggest that expanding midwifery practice in states with restrictive environments may significantly improve access to maternity care services.…”
Section: Chaptermentioning
confidence: 99%
“…They further suggest that expanding midwifery practice in states with restrictive environments may significantly improve access to maternity care services. In addition, CNMs and corresponding documentation for the rise of maternity care that strongly suggests the need for regulatory reform (Ranchoff & Declercq, 2020).…”
Section: Chaptermentioning
confidence: 99%
“…Slow recognition at the state and federal level of the full scope of midwifery practice persists. US midwifery was and continues to be caught in a web of conflicting laws, limitations on the ability to practice, and marginalization in health policy 9 . Midwifery practice is limited by state regulations that improperly define scope of practice, require supervisory or other professional agreements with physicians, and limit access to full staff privileges in hospital settings.…”
Section: Health Care In the United States: A Historical Lensmentioning
confidence: 99%
“…A profession's practice authority is related to the practitioners’ ability to practice across the full scope of their education and credentialing 12 . Increased practice authority for midwives and advanced practice nurses improves use of services and affects the size and demographics of the workforce without negatively impacting quality of care, thereby expanding client choice of practitioner and increasing access to care, particularly in medically underserved rural and urban areas 12‐18 …”
Section: State/ Territory Title Interconception Careb Oxytocin/pitocimentioning
confidence: 99%